Draft Ninth Five Year Plan (1997-2002) Andhra Pradesh Volume - II (Sectoral Programmes) 1. Agriculture and Allied Services - Planning Commission (Planning Commission, 1997)
Groundnut, Sesamum, Castor and Sunflower are important oilseeds crops with the thrust given to oilseeds crops, there has been considerable increase in oilseed production. But the area and production is fluctuating due to seasonal aberrations Groundnut alone accounts for about 80% of the oilseeds production in the state at 26.25 lakh tonnes followed by sunflower. There was slight shift in Groundnut area due to fanners favouring sunflower crop.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh